AN INVESTIGATION INTO THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ENHANCING ORAL PROFICIENCY OF ESL STUDENTS - Avazova Bibihadiqa Kholmakhmad qizi; Ilkhomova Umida Djamaliddinovna (Bright Mind Publishing, 2025)
Artificial Intelligence [AI] has revolutionized language learning by providing innovative tools to enhance speaking skills. This study explores the impact of AI-driven speech recognition technology, virtual conversation partners, and personalized learning platforms on English language learners. A qualitative research approach was adopted, utilizing a systematic literature review and thematic analysis to assess AI’s effectiveness in pronunciation improvement, fluency development, and learner confidence. The findings indicate that AI-based tools offer significant benefits, including real-time feedback, adaptive learning experiences, and autonomous speaking practice. However, the study also highlights limitations such as the lack of human interaction, contextual understanding challenges, and accessibility barriers. The results suggest that AI is most effective when integrated into a hybrid - learning model that combines automated feedback with human-led instruction. Future research should focus on improving AI’s ability to interpret conversational nuances, expanding accessibility, and enhancing engagement strategies to optimize AI-assisted speaking skill development.
Keywords: Artificial Intelligence, language learning, speaking skills, speech recognition, AI-based education, personalized learning, virtual conversation partners.